2021
DOI: 10.5853/jos.2021.02306
|View full text |Cite
|
Sign up to set email alerts
|

Clot Composition Analysis as a Diagnostic Tool to Gain Insight into Ischemic Stroke Etiology: A Systematic Review

Abstract: Mechanical thrombectomy renders the occluding clot available for analysis. Insights into thrombus composition could help establish the stroke cause. We aimed to investigate the value of clot composition analysis as a complementary diagnostic tool in determining the etiology of large vessel occlusion (LVO) ischemic strokes (International Prospective Register of Systematic Reviews [PROSPERO] registration # CRD42020199436). Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 134 publications
0
11
0
Order By: Relevance
“…Across all retrieved thrombus, 10 were retrieved by ADAPT technique, 20 by stent retrieved, and 64 by a combination of aspiration and stent retrieval. For NCCT analysis, the median thrombus attenuation was 50 (9), and the volume was 0.10 (0.21). For histopathological analysis, 12 of the retrieved thrombi were classified as red clots [red blood cell (RBC) dominant], 62 were classified as mixed clots (RBC equal to fibrin), 10 were classified as white clots (fibrin dominant), and the other 10 were classified as organized clots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all retrieved thrombus, 10 were retrieved by ADAPT technique, 20 by stent retrieved, and 64 by a combination of aspiration and stent retrieval. For NCCT analysis, the median thrombus attenuation was 50 (9), and the volume was 0.10 (0.21). For histopathological analysis, 12 of the retrieved thrombi were classified as red clots [red blood cell (RBC) dominant], 62 were classified as mixed clots (RBC equal to fibrin), 10 were classified as white clots (fibrin dominant), and the other 10 were classified as organized clots.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, their association with each other is essential for patients with AIS. If there is no such link, it would suggest that more advanced analyses such as microRNA signatures and proteomic analysis should be considered to elucidate the composition of the thrombus (9).…”
Section: Introductionmentioning
confidence: 99%
“…The TAT in subtypes of ischemic stroke differs depending on the underlying mechanism of embolus formation. Thrombosis in the coronary artery or heart cavity caused by rupture or fissuring of plaques or damage to the heart structure will flow and block the cerebral vessels, especially in atrial fibrillation [ 32 ]. Besides, compared with cerebrovascular, plentiful large clotting factors were activated in the heart blood vessel, more blood cells are recruited and a large amount of fibrinogen is activated, and then thrombi are formed.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: AMI, acute myocardial infarction: CT, computed tomography: DL, dyslipidemia: DM, diabetes mellitus: HTN, hypertension: ICA, internal carotid artery: IV-tPA, intravenous recombinant tissue plasminogen activator: MCA, middle cerebral artery: MRI, magnetic resonance imaging: N/A, not applicable: OTR, onset to reperfusion: PCI, percutaneous coronary intervention: RBC, red blood cell: SR, stent retriever eligible studies (97 cohort studies, 31 case reports, and 6 case series) has showed that the associations of thrombus size, structure, and composition with their etiology were inconsistent. 9) Meanwhile, there are no cohort studies examining the association between cholesterol crystals and embolic source in cerebral embolism. It is only stated on the premise that the thrombus containing them is atheroma in the studies that have assessed thrombectomy-induced wall damage, stiffness and elasticity of thrombus, or reperfusion rates.…”
Section: Discussionmentioning
confidence: 99%